Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

In order to find the derivative of a exponential function, on its general form $a^x$ by the definition, I used limits.

$\begin{align*} \frac{d}{dx} a^x & = \lim_{h \to 0} \left [ \frac{a^{x+h}-a^x}{h} \right ]\\ \\ & =\lim_{h \to 0} \left [ \frac{a^x \cdot a^h-a^x}{h} \right ] \\ \\ &=\lim_{h \to 0} \left [ \frac{a^x \cdot (a^h-1)}{h} \right ] \\ \\ &=a^x \cdot \lim_{h \to 0} \left [\frac {a^h-1}{h} \right ] \end{align*}$

I know that this last limit is equal to $\ln(a)$ but how can I prove it by using basic Algebra and Exponential and Logarithms properties? Thanks

share|improve this question
    
$a^h=\exp(\ln a \cdot h)$. Are you able to Taylor expand the exponential function? –  anon Oct 30 '11 at 23:33
    
Well, can we use the definition but be a bit witty? Perhaps we could use the definition (along with the chain rule) on $\log y = \log (a^x)$? –  mixedmath Oct 30 '11 at 23:43
    
I think it is worth mentioning that some authors (such as E. Landau) define the logarithm that way. –  Pedro Tamaroff May 2 '12 at 21:23
    
I consider this to be a rather tricky issue. Let me explain. Let $a$ be positive real number. Then to \textit{define} $a^x$ algebraically is easy on the rationals, just ask that the standard exponent laws hold. But if you want to define $a^x$ for irrational values, you need to do some analysis. In particular you need to prove that $a^x$ is continuous on the rationals. –  Baby Dragon Jun 3 '12 at 8:04

2 Answers 2

First, we prove it for $a=e$.

Let $\frac{1}{t} = e^h - 1$. Then $e^h = 1+\frac{1}{t}$, so $h = \ln(1 + \frac{1}{t})$. As $h\to 0$, we have $\frac{1}{t}\to 0$, so $t\to \infty$ (if $h\to 0^+$) or $t\to-\infty$ (if $h\to 0^-$). We have: $$\begin{align*} \lim_{h\to 0^+}\frac{e^h-1}{h} &= \lim_{t\to\infty}\left(\frac{1/t}{\ln(1+\frac{1}{t})}\right)\\ &= \lim_{t\to\infty}\frac{1}{t\ln(1+\frac{1}{t})}\\ &= \lim_{t\to\infty}\frac{1}{\ln\left( (1+\frac{1}{t})^t\right)}\\ &= \frac{1}{\ln\left(\lim_{t\to\infty}(1 + \frac{1}{t})^t\right)}\\ &= \frac{1}{\ln(e)}\\ &= 1. \end{align*}$$ Since we also have $$\begin{align*} \lim_{t\to-\infty}\left(1 + \frac{1}{t}\right)^t &= \lim_{n\to\infty}\left(1 - \frac{1}{n}\right)^{-n}\\ &= \lim_{n\to\infty}\frac{1}{(1 + \frac{-1}{n})^n}\\ &= \frac{1}{e^{-1}}\\ &= e,\end{align*}$$ a similar calculation shows that $$\lim_{h\to 0^-}\frac{e^h-1}{h} = 1.$$ Hence, $$\lim_{h\to 0}\frac{e^h-1}{h} = 1.$$

Now for arbitrary $a\gt 0$, $a\neq 1$, we rewrite $a^h = e^{h\ln(a)}$, and make the substitution $t = h\ln(a)$. Then the result follows from the case $a=h$ as Gerry Myerson shows.

share|improve this answer

It depends a bit on what you're prepared to accept as "basic algebra and exponential and logarithms properties". Look first at the case where $a$ is $e$. You need to know that $\lim_{h\to0}(e^h-1)/h)=1$. Are you willing to accept that as a "basic property"? If so, then $a^h=e^{h\log a}$ so $$(a^h-1)/h=(e^{h\log a}-1)/h={e^{h\log a}-1\over h\log a}\log a$$ so $$\lim_{h\to0}(a^h-1)/h=(\log a)\lim_{h\to0}{e^{h\log a}-1\over h\log a}=\log a$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.